Post‐operative infection of endoscopic submucosal dissection of early colorectal neoplasms: a case–controlled study using a Japanese database. (6th August 2015) - Muro, T.; Higuchi, N.; Imamura, M.; Nakagawa, H.; Honda, M.; Nakao, K.; Izumikawa, K.; Sasaki, H.; Kitahara, T.
Summary What is known and objective Endoscopic submucosal dissection of early colorectal neoplasms (ESD‐ECN) is known to be an operation with risk of contamination, possibly requiring pre‐operative antimicrobial prophylaxis for the prevention of post‐operative infection. However, an evaluation of the need for pre‐operative antimicrobial prophylaxis for ESD‐ECN has yet to be reported. The objective of this study was to determine whether pre‐operative antimicrobial prophylaxis is associated with a reduced incidence of post‐operative infection following ESD‐ECN. Methods The present retrospective case–controlled study utilized a database built from the medical records of 14 university hospitals throughout Japan. Patients who were admitted and discharged from the hospital from April 2012 to October 2013 and who had undergone ESD‐ECN were included in the study. Patients who had been undergone any other operation during their course of hospitalization, and patients who were prescribed antimicrobial agents for reasons other than post‐operative infection or for prophylaxis were excluded. Characteristics of the study population, pre‐operative antimicrobial prophylaxis and antimicrobial therapy for post‐operative infection were investigated. In addition, we compared the characteristics of patients with post‐operative infection (PI) and those with no post‐operative infection (NPI). Univariate analyses were used to estimate the odds ratios (OR) and 95% confidence intervals (95% CI). Results and discussion We obtained the records of 522 patients who had undergone ESD‐ECN from the database. After application of exclusion criteria, 421 patients were enrolled. The post‐operative infection rate was 1·2%. Peritonitis was found most to be the most common post‐operative infection (44%). Pre‐operative antimicrobial prophylaxis was used for 314 patients (75%), with a median duration of 3·0 (range 1–11) days. Cefotiam was most frequently prescribed for pre‐operative antimicrobial prophylaxis (56%). Antimicrobial therapies were started 1–10 days after ESD‐ECN for a duration of 1–14 days. Pre‐operative antimicrobial prophylaxis was not associated with post‐operative infection rate, with an OR (95% CI) of 0·73 (0·08–6·61). However, digestive tract perforation was shown to be associated with post‐operative infection and had an OR (95% CI) of 17·1 (1·66–176·45). What is new and conclusion Post‐operative infection is an exceedingly rare event following ESD‐ECN. Pre‐operative antimicrobial prophylaxis had no significant effect on post‐operative infection following ESD‐ECN and thus may be unnecessary. Instead, prevention of digestive tract perforation may be more critical for the decrease in post‐operative infections.